Forest Insect Biosecurity: Processes, Patterns, Predictions, Pitfalls - Nahrung, Helen F; Liebhold, Andrew M; Brockerhoff, Eckehard G; Rassati, Davide (Annual review of entomology, 2023)
The economic and environmental threats posed by non-native forest insects are ever increasing with the continuing globalization of trade and travel; thus, the need for mitigation through effective biosecurity is greater than ever. However, despite decades of research and implementation of preborder, border, and postborder preventative measures, insect invasions continue to occur, with no evidence of saturation, and are even predicted to accelerate. In this article, we review biosecurity measures used to mitigate the arrival, establishment, spread, and impacts of non-native forest insects and possible impediments to the successful implementation of these measures. Biosecurity successes are likely under-recognized because they are difficult to detect and quantify, whereas failures are more evident in the continued establishment of additional non-native species. There are limitations in existing biosecurity systems at global and country scales (for example, inspecting all imports is impossible, no phytosanitary measures are perfect, knownunknowns cannot be regulated against, and noncompliance is an ongoing problem). Biosecurity should be a shared responsibility across countries, governments, stakeholders, and individuals.
Keywords: Animals; phytosanitary measures; biologická bezpečnost; Forests; eradication; non-native species; Internationality; surveillance; biological invasions; zvířata; pathways; hmyz; Introduced Species; zavlečené druhy; internacionalita; Insecta; Biosecurity; lesy